Anatomy of the Islam Nusantara Program and the Necessity for a “Critical” Islam Nusantara Study - Masaaki, Okamoto (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2020)
This paper examines the Islam Nusantara graduate program established by the Islamic Studies Institute of Nahdlatul Ulama (Stainu) in 2013 and later continued by the Nahdlatul Ulama University of Indonesia (Unusia). As the largest Islamic social organization in Indonesia, Nahdlatul Ulama (NU) has articulated Islam Nusantara as a framework emphasizing moderation, tolerance, and the accommodation of local cultures, particularly as a response to the strengthening conservative turn in Indonesian Islam following the country’s democratic transition in 1998. To institutionalize and disseminate this perspective, NU founded a dedicated graduate program focusing on Islam Nusantara. After outlining the rise of Islamic conservatism and the promotion of Islam Nusantara by both NU and the state, this study analyzes graduate theses produced within the program by examining their abstracts and the socio-demographic backgrounds of their authors. The findings show that the majority of thesis authors are young scholars, predominantly male and Java-born, and that many theses focus on harmonious forms of Islamic adaptation to local cultures, often centered on the authors’ regions of origin. The paper concludes by emphasizing the need for more comparative and critical approaches to local variations of Islam Nusantara in future theses and dissertations, in order to enable the program to engage more reflexively and analytically with the concept of Islam Nusantara itself.